Etoposide and topoisomerase II inhibition for aggressive prostate cancer: Data from a translational study. - Carlo Cattrini; Matteo Capaia; Francesco Boccardo; Paola Barboro (Cancer Treatment and Research Communications, 2020)
Background: Etoposide phosphate (VP-16) is a topoisomerase 2 (TOP2) inhibitor that demonstrated activity in patients with metastatic castration-resistant prostate cancer (mCRPC). We investigated the sensitivity of prostate cancer (PCa) cells (LNCaP, 22Rv1, PC3, DU145, PDB and MDB) to VP-16 and the possible relationship between VP-16 activity and TOP2 expression. The activity of VP-16 was compared with that of docetaxel, enzalutamide and olaparib. The prevalence and clinical significance of TOP2 genetic and transcriptomic alterations was also explored in mCRPC. Methods: Cell cultures and crystal violet cell proliferation assays were performed. Specific antibodies were used in western blots analyses of cell protein extracts. Datasets were analyzed in cBioportal. Results: VP-16 was active in all PCa cell lines analyzed and demonstrated increased activity in PC3 and DU145 cells. VP-16 was more cytotoxic compared to the other treatments, except for LNCaP and 22Rv1, which were more sensitive to docetaxel. Maintenance of antiandrogen treatment in MDB and PDB increased sensitivity to VP-16, docetaxel and enzalutamide. TOP2A was found overexpressed in 22Rv1, DU145 and PC3, whereas TOP2B was overexpressed in 22Rv1 and PDB. In the mCRPC datasets analysis, TOP2A mRNA overexpression was associated with worse patients’ prognosis, with the molecular features of neuroendocrine prostate cancer (NEPC) and with lower androgen receptor (AR) score. Patients overexpressing TOP2A mRNA were more likely to harbor RB1 loss. Conclusions: Specific subpopulations of patients with aggressive variant prostate cancer (AVPC) could benefit from VP-16 treatment. TOP2A overexpression, rather than TOP2B, might be a good biomarker to predict response to VP-16.